Osteochondral Allografts in the Ankle Joint: State of the Art. (July 2013) - Vannini, Francesca; Buda, Roberto; Pagliazzi, Gherardo; Ruffilli, Alberto; Cavallo, Marco; Giannini, Sandro
Purpose: The aim of this systematic review is to report about the clinical use of partial and total fresh osteochondral allograft in the ankle joint. The state of the art of allografts with regard to basic science, procurement and storage methods, immunogenicity, generally accepted indications and contraindications, and the rationale of the allografting procedure have been described. Methods: All studies published in PubMed from 2000 to January 2012 addressing fresh osteochondral allograft procedures in the ankle joint were identified, including those that fulfilled the following criteria: (a) level I-IV evidence addressing the areas of interest outlined above; (b) measures of functional, clinical, or imaging outcome; and (c) outcome related to ankle cartilage lesions or ankle arthritis treated by allografts. Results: The analysis showed a progressively increasing number of articles from 2000. The number of selected articles was 14; 9 of those focused on limited dimension allografts (plugs, partial) and 5 on bipolar fresh osteochondral allografts. The evaluation of evidence level showed 14 case series and no randomized studies. Conclusions: Fresh osteochondral allografts are now a versatile and suitable option for the treatment of different degrees of osteochondral disease in the ankle joint and may even be used as total joint replacement. Fresh osteochondral allografts used for total joint replacement are still experimental and might be considered as a salvage procedure in otherwise unsolvable situations. A proper selection of the patients is therefore a key point. Moreover, the patients should be adequately informed about the possible risks, benefits, and alternatives to the allograft procedure.